Brucella ceti : THE Threat of Emerging Zoonoses in Indo Pacific Bottle Nose (Tursiops aduncus) - Agustin Indrawati; Usama Affif (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Incidence of Brucellosis in marine mammals in the world is found lately particularly in Penniped and Cetacea. Indonesia is an archipelago that is rich with its Wildlife and one of them is Indo Pacific bottle nose dolphins (Tursiops aduncus). In this research, Indo Pasific bottle nose dolphins (Tursiops aduncus) were used deriving from captive of marine mammal conservation in Indonesia PT Wersut Seguni. All of them were in good condition. A total of 23 blood samples collected from the caudal vein, located above the tail fin. Blood samples was taken as Aseptic as possible. Screening test against Brucella spp was done by Rose Bengal Test (RBT) and Rapid Test B. Brucella. One sample out of 23 samples had antibody positif against Brucella spp (4%). The results of this research concluded that Brucella spp found is likely to be Brucella Ceti . It is also found in Indonesia territorial and in the Indo Pacific bottle nose dolphins (Tursiops aduncus). We hope that this finding will do raise our awerness to emerging zoonoses.Keywords: brucellosis, Brucella ceti, RBT, Rapid test, Tursiops aduncus